Amphiphilic Cytosolic Glycans from Mycobacteria: Occurrence, Lipid‐Binding Properties, Biosynthesis, and Synthesis. Issue 10 (27th July 2013) - Xia, Li; Lowary, Todd L.; Bush, C. Allen
ABSTRACT Polymethylated polysaccharides (PMPSs), glycans composed of 10–20 carbohydrate residues the majority of which carry a single methyl group, are produced by some mycobacterial species. O‐Methylation thus occurs on 20–30% of all the hydroxyl groups within the molecule, rendering them amphiphilic. A property of PMPSs is their ability to form high‐affinity complexes with fatty acids and their derivatives, suggesting a role in mycobacterial fatty acid biosynthesis. However, direct evidence for their in vivo function is still lacking. Over the past several decades the lipid‐binding properties, biosynthesis, and chemical synthesis of PMPSs have been explored and this review will provide an overview of progress made in these areas. © 2013 Wiley Periodicals, Inc. Biopolymers 99: 697–712, 2013.